High performance work systems and perceived organizational support: The contribution of human resource department's organizational embodiment - Kim, Kyoung Yong; Clark, Kevin D.; Messersmith, Jake G. (Human Resource Management, 2023)
Abstract Integrating the literatures on strategic human resource management and organizational support theory, we examine the cross‐level relationship between high performance work systems (HPWS) at the team‐level and individual perceptions of organizational support (i.e., POS). In addition, we introduce a critical boundary condition, the HR department's organizational embodiment (HROE), which involves the extent to which employees identify the HR department with the organization. We propose that the cross‐level HPWS–POS relationship is moderated by HROE, such that the linkage between HPWS and POS is stronger when HROE is high. With a sample of 103 teams and 399 employees in South Korea, we find that HPWS utilization increases POS and that this relationship is stronger when HROE is high. We also find that HR department status and the favorable attitude of the HR head are antecedents to HROE. These findings suggest that HROE is a critical boundary condition for the relationship between HPWS and POS with subsequent effects on organizational commitment and job satisfaction.